Exploring Medicinal Herbs’ Therapeutic Potential and Molecular Docking Analysis for Compounds as Potential Inhibitors of Human Acetylcholinesterase in Alzheimer’s Disease Treatment - Ayoub Farihi; Mohamed Bouhrim; Fatiha Chigr; Amine Elbouzidi; Noureddine Bencheikh; Hassan Zrouri; Fahd A. Nasr; Mohammad Khalid Parvez; Ahmad Alahdab; Ahmed Omar Touhami Ahami (Medicina, 2023)
Background and Objectives: Alzheimer’s disease (AD) stands as a pervasive neurodegenerative ailment of global concern, necessitating a relentless pursuit of remedies. This study aims to furnish a comprehensive exposition, delving into the intricate mechanistic actions of medicinal herbs and phytochemicals. Furthermore, we assess the potential of these compounds in inhibiting human acetylcholinesterase through molecular docking, presenting encouraging avenues for AD therapeutics. Materials and Methods: Our approach entailed a systematic exploration of phytochemicals like curcumin, gedunin, quercetin, resveratrol, nobiletin, fisetin, and berberine, targeting their capability as human acetylcholinesterase (AChE) inhibitors, leveraging the PubChem database. Diverse bioinformatics techniques were harnessed to scrutinize molecular docking, ADMET (absorption, distribution, metabolism, excretion, and toxicity), and adherence to Lipinski’s rule of five. Results: Results notably underscored the substantial binding affinities of all ligands with specific amino acid residues within AChE. Remarkably, gedunin exhibited a superior binding affinity (−8.7 kcal/mol) compared to the reference standard. Conclusions: These outcomes accentuate the potential of these seven compounds as viable candidates for oral medication in AD treatment. Notably, both resveratrol and berberine demonstrated the capacity to traverse the blood-brain barrier (BBB), signaling their aptitude for central nervous system targeting. Consequently, these seven molecules are considered orally druggable, potentially surpassing the efficacy of the conventional drug, donepezil, in managing neurodegenerative disorders.